A novel atomic movement mechanism of intersection-induced bct-α → bcc-α′ martensitic phase transformation. (November 2021) - Fu, Hui; Yuan, Shuqing; Sun, Wanting; Wan, Jianquan; Chan, K.C.; Zhu, Jiaming; Yang, Xu-Sheng
Abstract: The atomic movements for completing the fcc-γ → hcp-ε → bct-α Plastic Deformation-Induced Martensitic Transformation (PDIMT) has been revealed to be confined purely on one specific { 111 } γ plane. However, so far nothing has been known for the possible intersection of two fcc-γ → hcp-ε → bct-α PDIMTs pre-developed from two individual { 111 } γ slip systems. For the first time, here we capture the nucleation of bcc-α′ in the intersection of two bct-α phases in 304 stainless steel, following a novel polymorphic fcc-γ → hcp-ε → bct-α → bcc-α′ PDIMT. High-resolution transmission electron microscopy observations were mainly performed to unveil the underlying atomic process in the final-step bct-α → bcc-α′ transition, which is executed by the cooperation of partial dislocation dipoles gliding on every second { 110 } α planes of two bct-α phases (equivalent to { 110 } α ′ and { 011 } α ′ planes), and atom shuffling along the [ 1 1 ¯ 0 ] α 1 / [ 1 ¯ 12 ] α ′ and [ 1 1 ¯ 0 ] α 2 / [ 21 1 ¯ ] α ′ directions.